COVID-19 alert level systems—Lessons learnt for future public health emergencies: A qualitative study - Hana Rohan; Aaron F. Bochner; Lauren Brown; Elizabeth M. Ortiz; Amanda McClelland (PLoS ONE, 2026)
Background During the COVID-19 pandemic, Alert Level Systems (ALS) were widely implemented as public health tools to communicate risk levels and recommend public health and social measures (PHSMs). However, the efficacy of ALS in mitigating disease spread and their impact on public health responses have not been systematically evaluated. This study aims to assess perceptions of ALS implementation across diverse jurisdictions and derive lessons for future public health emergencies. Methods Key informant interviews were conducted remotely between December 2023 and March 2024 with senior stakeholders who were involved in ALS development and implementation during the COVID-19 pandemic, from eight jurisdictions: California (US), New Zealand, the Philippines, Rio Grande do Sul (Brazil), Singapore, South Africa, the United Kingdom, and the United States. A thematic analysis approach was applied to synthesize insights, focusing on the strengths, challenges, and key lessons from ALS implementation. Results ALS were generally perceived by key informants as useful tools for communicating risk and supporting adherence to PHSMs due to their simplicity and transparency. However, significant challenges were identified, including difficulties in accessing reliable data, lack of clear ALS objectives, and insufficient community engagement. The study highlights the need for ALS to integrate social, economic, and epidemiological data in decision-making processes. Jurisdictions also reported that pre-existing ALS governance structures and stronger community feedback mechanisms could have improved implementation outcomes. Conclusions ALS can serve as valuable public health communication tools in future epidemics, but their success depends on clear objectives, evidence-based PHSMs, and robust community engagement. Pre-emptive development of ALS structures and governance will improve preparedness for future epidemics. Transparent and flexible decision-making processes will be crucial for sustaining public trust.